Therapeutic potential of mesenchymal stem cells transplantation on traumatic facial nerve paralysis in two horses - de Oliveira Ferreira, Lucas Vinícius [UNESP]; Maia, Leandro [UNESP]; de Andrade, Danilo Giorgi Abranches [UNESP]; da Costa Kamura, Beatriz [UNESP]; de Carvalho, Márcio [UNESP]; Amorim, Rogério Martins [UNESP] (Springer Nature, 2025)
Cell-based therapy has emerged as a promising strategy for treating peripheral nervous system (PNS) injuries across different species. However, there is a scarcity in the literature regarding the transplantation of mesenchymal stem cells (MSCs) for treating PNS injuries in horses. This report aims to describe the therapeutic potential of equine MSC transplantation in two horses with chronic traumatic facial nerve paralysis. Both horses presented with lip ptosis and right deviation of the nostril and upper lip, being clinically diagnosed with left facial nerve paralysis. Due to the refractoriness to conventional anti-inflammatory treatments, cell-based therapy was chosen. One horse received an autologous transplant of equine bone marrow-derived MSCs (EqBM-MSCs) four months after the traumatic event, while the other underwent three transplants of allogeneic equine adipose tissue-derived MSCs (EqAT-MSCs) at 30-day intervals, starting two months after the injury. All transplants were performed at three different sites around the facial nerve, at the level of bifurcation of the buccal branch in both horses. Physical and neurological assessments revealed significant clinical recovery within three months for the first horse and four months for the second. These findings demonstrated that equine MSCs transplants have great therapeutic potential for chronic traumatic facial nerve paralysis in horses, highlighting the relevance of MSCs- based therapy for peripheral nerve injuries.
Keywords: Adipose tissue; Bone marrow; Cell-based therapy; Cranial nerve; Equine